2003
DOI: 10.1002/humu.10225
|View full text |Cite
|
Sign up to set email alerts
|

Mutant NDUFV2 subunit of mitochondrial complex I causes early onset hypertrophic cardiomyopathy and encephalopathy

Abstract: Respiratory chain complex I deficiencies represent a genetically heterogeneous group of diseases resulting from mutations in either mitochondrial or nuclear DNA. Combination of denaturing high performance liquid chromatography and sequence analysis allowed us to show that a 4-bp deletion in intron 2 (IVS2+5_+8delGTAA) of the NDUFV2 gene (encoding NADH dehydrogenase ubiquinone flavoprotein 2) causes complex I deficiency and early onset hypertrophic cardiomyopathy with trunk hypotonia in three affected sibs of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
94
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(98 citation statements)
references
References 26 publications
2
94
1
1
Order By: Relevance
“…Our interpretation is supported from the findings that mutations in the mitochondrial signal sequence of the precursor of the 24-kDa subunit of complex I, which may influence the levels of the protein in mitochondria, result in increased susceptibility to Parkinson's disease (Hattori et al 1998). Other mutations that lower the mitochondrial amounts of the 24-kDa polypeptide (Benit et al 2003) and of other complex I subunits were found as well.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Our interpretation is supported from the findings that mutations in the mitochondrial signal sequence of the precursor of the 24-kDa subunit of complex I, which may influence the levels of the protein in mitochondria, result in increased susceptibility to Parkinson's disease (Hattori et al 1998). Other mutations that lower the mitochondrial amounts of the 24-kDa polypeptide (Benit et al 2003) and of other complex I subunits were found as well.…”
Section: Discussionsupporting
confidence: 78%
“…During the past years, several specific point mutations in nuclear genes have been discovered, specifically in those coding for the human homologs of the 75-kDa (Benit et al 2001), 51-kDa (Schuelke et al 1999), 49-kDa (Loeffen et al 2001), 30-kDa (Benit et al 2004), 24-kDa (Benit et al 2003), TYKY (Loeffen et al 1998), PSST (Triepels et al 1999), AQDQ (van den Heuvel et al 1998), and IP13 (Kirby et al 2004) subunits of complex I. Mimicked in our study are two compound heterozygous mutations in TYKY (P79L and R102H) and a homozygous mutation in PSST (V122M) in patients suffering from Leigh syndrome (Loeffen et al 1998;Triepels et al 1999), as well as mutations in the 51-kDa polypeptide involved in the development of leukodystrophy and myoclonic epilepsy (associated with a homozygous A341V mutation and a compound heterozygous T423M and R59X mutation) (Schuelke et al 1999). These three proteins have homologs in the fungus N. crassa, namely the 21.3c-kDa (Duarte et al 1996), 19.3-kDa (Sousa et al 1999, and 51-kDa (Preis et al 1991) subunits, respectively, and are highly conserved from bacteria to mammals.…”
mentioning
confidence: 99%
“…Seven of the subunits of Complex I are encoded by the mitochondrial genome, while the remaining 39 subunits are products of nuclear genes. Mutations identified in genes encoding for complex I subunits have been associated with complex I disassembly, instability and increase in reactive oxygen species production, resulting in degenerative diseases (Benit et al, 2003;Kirby et al, 2004;Loeffen et al, 2001;Mamelak et al, 2005). In the present study no significant alteration in expression of the mtDNA coded genes that are included in the Affymetrix Rat Genome 230 2.0 were found, whereas expression of 16 out of the 37 genes coded by the nDNA was decreased.…”
Section: Discussioncontrasting
confidence: 58%
“…In most cases, CI deficiency is caused by autosomal recessive mutations involving subunits encoded by the nuclear genome (55). So far, mutations have been demonstrated in the NDUFV1, NDUFV2, NDUFS1, NDUFS2, NDUFS3, NDUFS4, NDUFS6, NDUFS7, and NDUFS8 subunit of CI and the chaperone/assembly factor B17.2L (4,5,9,25,28,40). In our research, we aim to understand the regulatory principles underlying mitochondrial function at the molecular level.…”
mentioning
confidence: 99%